A systematic approach to pipe-in-pipe installation analysis - Jiwa, M.Z. (Elsevier Ltd, 2017)
In the present study, the selection of a pipe-in-pipe (PIP) system which includes an installation analysis modelling technique is investigated. The PIP system has become the standard pipeline design for subsea field developments, especially for deep water fields. One of the most important design challenges for engineers is the pipeline installation design. A design underestimation of loads could result in serious damage, while overestimation would result in high operation costs. An accurate or improved modelling method is definitely required for the PIP system. The modelling of a finite element single pipe-lay simulation has been studied and discussed by many authors, and is very much understood by the people in the industry. However, modelling complex PIP systems for pipe laying simulations in order to obtain accurate results is quite challenging. To build the most economic finite element (FE) model for the pipe-lay simulation of PIP systems, various modelling aspects of the installation have been studied separately. In this work, three types of FE models which are two models with different simplifications and one actual PIP model were established and compared. Finally, a systematic approach selection for performing a PIP installation is presented. © 2017 Elsevier Ltd